2017
DOI: 10.3390/su9122302
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugation of Digestate: The Effect of Chitosan on Separation Efficiency

Abstract: Mechanical separation of co-digestate removes dry matter (DM) and phosphorous (P) from digestate effectively but is less capable at removing nitrogen (N) and potash (K). Adding flocculants can enhance separator efficiency. However, information on the use of chitosan as flocculant for co-digestate and its effects on amended slurry application to soil is scarce. This study undertook a series of trial and error tests to identify the optimal chitosan dose to be applied to co-digestate. Four chitosan doses were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…In particular, the mechanical separation is less capable of removing total K and NO 3 − as they appeared higher in content in LD sep 1.04 g/kg and 9.81 mg/kg compared to SFD sep 0.43 g/kg and 7.82 mg/kg, respectively. These findings are in agreement with those of a study by Popovic et al, who found that the separation efficiency can be enhanced by the addition of flocculants [33]. In the case of macronutrients Ca, Mg, S, and total N, mechanical separation with sieves (SFD sep ) was more effective for their transfer to the solid digestate in contrast to centrifugal separation (SFD dec ), which showed a better efficacy for Na, total P, and total K. Concerning trace elements and heavy metals, Hg, Cu, and B were better transferred to solid digestate using mechanical separation contrary to centrifugation, but the application of chitosan could increase centrifugation efficiency according to the results of Popovic et al [33].…”
Section: Evaluation Of Datasupporting
confidence: 94%
“…In particular, the mechanical separation is less capable of removing total K and NO 3 − as they appeared higher in content in LD sep 1.04 g/kg and 9.81 mg/kg compared to SFD sep 0.43 g/kg and 7.82 mg/kg, respectively. These findings are in agreement with those of a study by Popovic et al, who found that the separation efficiency can be enhanced by the addition of flocculants [33]. In the case of macronutrients Ca, Mg, S, and total N, mechanical separation with sieves (SFD sep ) was more effective for their transfer to the solid digestate in contrast to centrifugal separation (SFD dec ), which showed a better efficacy for Na, total P, and total K. Concerning trace elements and heavy metals, Hg, Cu, and B were better transferred to solid digestate using mechanical separation contrary to centrifugation, but the application of chitosan could increase centrifugation efficiency according to the results of Popovic et al [33].…”
Section: Evaluation Of Datasupporting
confidence: 94%
“…To intensify this process flocculation can be used based on the addition of different chemicals capable to increase the sizes of particles, which form flocs and increase floc resistance to further mechanical separation. The addition of chitosan as a new type of flocculent followed by centrifugation produced 27% solid fraction (8.8% dry matter) that improved centrifugation efficiency for K, Cu, and Zn and had no effect on total N or P [Popovic et al, 2017].…”
Section: Investigation Of the Dewatering Technologies Of The Digestatementioning
confidence: 99%
“…Therefore, chitosan is one of the most promising natural flocculants. Moreover, chitosan can form complexes with metallic ions [74]. Some studies explored the combined application of natural and synthetic chemicals in CEPT.…”
Section: Flocculants Used In Ceptmentioning
confidence: 99%